The Effect of Transactional Leadership, Organizational Commitment and Career Development on Employee Job Satisfaction With Work Motivation as an Intervening Variable in the Agency Regional Finance and Asset Management Karimun Regency - Riduan SIHITE; Chablullah WIBISONO; I Wayan CATRAYASA; Bambang SATRIAWAN (PT Keberlanjutan Strategis Indonesia, 2024)
The Karimun Regional Government issued a policy to extend the contracts of 75 contract workers out of the 80 contract workers in BPKAD Karimun Regency. Contrary to this policy, thousands of ASNs in Karimun Regency have only paid their salaries, which has an impact on decreasing employee satisfaction, which results in increasing employee absences without explanation. This quantitative research analyzes the relationship between transactional leadership, organizational commitment, career development, job satisfaction, and work motivation as intervening variables. It was concluded that transactional leadership and work motivation had a significant effect on job satisfaction, and job satisfaction significantly impacted work motivation. Organizational commitment and career development do not significantly affect job satisfaction. Organizational commitment does not substantially affect work motivation, while career development has a significant effect. Then transactional leadership and career development have a significant effect on job satisfaction when intervened by work motivation, while organizational commitment does not have a significant impact on job satisfaction when intervened by work motivation. It is recommended that leaders at the Karimun Regency BPKAD agency increase employee liking for the work given, support from colleagues in achieving targets, opportunities for promotion and work monitoring systems by employee and work conditions through, among other things, providing rewards for employee performance, creating and ensuring implementing regulations that can control employee safety and comfort, optimizing the provision of employee human standards, fair treatment at work, increasing employee awareness and understanding of career opportunities in the agency.